A novel cluster-based traffic analysis using trust computation in mobile ad hoc network - Dheepak, T.; Neduncheliyan, S. (International Journal of Engineering and Technology, 2019)
Mobile Ad-hoc Network (MANET) is a wireless network which is mobile and is deployed for an immediate or short-term purpose. MANETs operate by sharing information among its neighbors. Every node in a MANET utilizes responsibility for information flow since central coordination is absent. Hence, every node in a MANET completely trusts its neighbors for information distribution. Nodes in a MANET are vulnerable to several security threats which seek to use the weaknesses of the network. In this paper, a novel cluster-based traffic analysis is a reactive on-demand method for secured routing. This proposed methodology explains the method to overcome the traffic in the MANET by using trust-based cluster method.
Keywords: MANET; Traffic Analysis; Clustering; Trust Calculation; Reactive; on-Demand.